Safety evaluation of long-term temperature controlled whole-body thermal treatment in female Aachen minipig. (1st January 2021) - Carneiro, Marcia Weber; Brancato, Luigi; Wylleman, Britta; van Zwol, Eke; Conings, Liesbet; Vueghs, Peter; Gorbaslieva, Ivana; Van den Bossche, Johan; Rudenko, Oleg; Janicot, Michel; Bogers, John-Paul
Abstract: Objective: Thermal treatment (TT), defined as treatment using supra-physiological body temperatures (39–45 C), somewhat resembles fever in terms of temperature range, one of the first natural barriers for the body to fight exposure to external pathogens. Methods: Whole-body thermal treatment (WBTT) consists of heating up the complete body to a temperature range of 39 to 45 C. Despite the recognized therapeutic potential of hyperthermia, the broad clinical use of WBTT has been limited by safety issues related to medical devices and procedures used to achieve WBTT, in particular adequate control of the body temperature. To circumvent this, a sophisticated medical device was developed, allowing long-term temperature controlled WBTT (41.5 C for up to 8 h). Technical feasibility and tolerability of the WBTT procedure (including complete anesthesia) were tested using female Aachen minipig. Optical fiber temperature sensors inserted in multiple organs were used and demonstrated consistent monitoring and control of different organs temperature over an extended period of time. Results: Clinical evaluation of the animals before, during and after treatment revealed minor clinical parameter changes, but all of them were clinically acceptable. These changes were limited and reversible, and the animals remained healthy throughout the whole procedure and follow-up. In addition, histopathological analysis of selected key organs showed no thermal treatment-related changes. Conclusion: It was concluded that WBTT (41.5 C for up to 8 h) was well tolerated and safe in female Aachen minipigs. Altogether, data supports the safe clinical use of the WBTT medical device and protocol, enabling its implementation into human patients suffering from life-threatening diseases.